In vivo comparison of crestal bone heights following implant placement with "Flapless" and "Flap" techniques in the sites of early loaded implants - Suhani Kukreja Pahuja; Pooja Negi; Anjali Singh; Gangesh Bahadur Singh; Deepa Rayast; Manisha Minz (Wolters Kluwer Medknow Publications, 2021)
Purpose: The purpose was to evaluate the difference in crestal bone loss (CBL) around implants with flap and flapless methods followed by early loading. Materials and Methods: Twenty implants were placed in twenty patients - ten using flap and ten using flapless techniques. The difference in CBL was measured on standardized digital periapical radiograph taken at 0 week, 6 weeks, 12 weeks, and 6 months. Results: The present study showed the mean CBL on proximal surfaces when evaluated at intervals of 0 week, 6 weeks, 12 weeks, and 6 months for flapless method was significantly lower than with flap method the values of which were +0.07 mm against +0.26 mm on mesial side and +0.15 mm against +0.33 mm on distal side at 6 months. Conclusion: The flapless approach is a predictable procedure when patient selection and surgical technique are appropriate, and results in lesser CBL.